Unaddressed regulatory issues in xenotransplantation: a hypothetical example - Kwisda, Koko (Frontiers in Transplantation, 2023)
The last few years have seen a significant increase in the use of technology to manipulate genetic sequences and generate animals as a source of xeno-organs. This has made the generation of genetically bespoke organisms a reality. This paper will analyze the regulatory and practical aspects of such an innovative approach to xenotransplantation on the basis of a hypothetical case study applied to Germany and highlight the gaps in the current regulation. This paper thus provides the basis for legal debate within a specific country. In addition, the identified gaps also pose a barrier toward the harmonization of international regulation. This publication therefore lays the groundwork for guiding the international debate regarding the regulatory framework for solid organ xenotransplantation toward specific issues.